Effects of pragmatics awareness instruction (PAI) in enhancing EFL learners’ communicative competence - Mihretu Yihunie Yalew; Dawit Amogne; Birhanu Simegn Chanie (Cogent Education)
This study investigated the effects of pragmatics awareness instruction (PAI) in enhancing EFL learners’ communicative competence. The PAI metalanguage and metapragmatic description tasks and activities play a pivotal role in enhancing EFL learners’ communicative competence. Two intact group freshman students of Bahir Dar University, Ethiopia registered for ‘Communicative English Language Skills II, FLEn1012’ participated as the comparison group (CG) and interventional group (IG) participants of the study. While the CG participants were taught the FLEn1012 course using the conventional CLT approach, the IG participants were taught the same course using the metalanguage and metapragmatic description of tasks and activities. The collected pretest and posttest data were analysed using the t-test statistical analysis. The result from the IG participants was found statistically significant with a p-value, of p < 0.001; which is statistically significant with more than 99% probability of confidence and 1% probability of error. Similarly, the effect size of the IG was reported as d = 0.8 and above; which implies there was a strong positive effect relationship between PAI intervention and learners’ communicative competence improvement. The results signify that the IG participants who were taught using PAI significantly outperformed their CG counterparts who were taught using the conventional CLT approach. This implies that the incorporation of PAI into the CLT approach in EFL could have significant positive effects on learners’ communicative competence improvement. Further research should be conducted on the effects of incorporating PAI in EFL in enhancing learners’ communicative competence development.